SMRT and NCoR1 fine-tune inflammatory versus tolerogenic balance in dendritic cells by differentially regulating STAT3 signaling - Jha, Atimukta; Ahad, Abdul; Mishra, Gyan Prakash; Sen, Kaushik; Smita, Shuchi; Minz, Aliva Prity; Biswas, Viplov Kumar; Tripathy, Archana; Senapati, Shantibhushan; Gupta, Bhawna; Acha-Orbea, Hans; Raghav, Sunil Kumar (Frontiers in Immunology, 2022)
Dendritic cell (DC) fine-tunes inflammatory versus tolerogenic responses to protect from immune-pathology. However, the role of co-regulators in maintaining this balance is unexplored. NCoR1-mediated repression of DC immune-tolerance has been recently reported. Here we found that depletion of NCoR1 paralog SMRT (NCoR2) enhanced cDC1 activation and expression of IL-6, IL-12 and IL-23 while concomitantly decreasing IL-10 expression/secretion. Consequently, co-cultured CD4+ and CD8+ T-cells depicted enhanced Th1/Th17 frequency and cytotoxicity, respectively. Comparative genomic and transcriptomic analysis demonstrated differential regulation of IL-10 by SMRT and NCoR1. SMRT depletion represses mTOR-STAT3-IL10 signaling in cDC1 by down-regulating NR4A1. Besides, Nfkbia and Socs3 were down-regulated in Ncor2 (Smrt) knockdown cDC1, supporting increased production of inflammatory cytokines. Moreover, studies in mice showed, adoptive transfer of SMRT knockdown cDC1 in OVA-DTH induced footpad inflammation led to increased Th1/Th17 and reduced tumor burden after B16 melanoma injection by enhancing oncolytic CD8+ T-cell frequency, respectively. We also depicted decreased Ncor2 expression in Rheumatoid Arthritis, a Th1/Th17 disease.